Data from: A grazing Gomphotherium in Middle Miocene Central Asia, 10 million years prior to the origin of the Elephantidae - Wu, Yan; Deng, Tao; Hu, Yaowu; Ma, Jiao; Zhou, Xinying; Mao, Limi; Zhang, Hanwen; Ye, Jie; Wang, Shi-Qi (Dryad, 2018)
Feeding preference of fossil herbivorous mammals, concerning the
coevolution of mammalian and floral ecosystems, has become of key research
interest. In this paper, phytoliths in dental calculus from two
gomphotheriid proboscideans of the middle Miocene Junggar Basin, Central
Asia, have been identified, suggesting that Gomphotherium connexum was a
mixed feeder, while the phytoliths from G. steinheimense indicates grazing
preference. This is the earliest-known proboscidean with a predominantly
grazing habit. These results are further confirmed by microwear and
isotope analyses. Pollen record reveals an open steppic environment with
few trees, indicating an early aridity phase in the Asian interior during
the Mid-Miocene Climate Optimum, which might urge a diet remodeling of G.
steinheimense. Morphological and cladistic analyses show that G.
steinheimense comprises the sister taxon of tetralophodont gomphotheres,
which were believed to be the general ancestral stock of derived “true
elephantids”; whereas G. connexum represents a more conservative lineage
in both feeding behavior and tooth morphology, which subsequently became
completely extinct. Therefore, grazing by G. steinheimense may have acted
as a behavior preadaptive for aridity, and allowing its lineage evolving
new morphological features for surviving later in time. This study
displays an interesting example of behavioral adaptation prior to
morphological modification.
Supplementary dataset 6.1txt format fle for the maximum parsimony
analysisSupplementary dataset 6.2xlsx format fle for the pollen data